Efektivitas Pemanfaatan Dana Bantuan Operasional Penyelenggaraan Pendidikan Anak Usia Dini (BOP PAUD) Di Dinas Pendidikan Kota Tangerang - Indi Rahmawati; Putri Alika; Ila Rosmilawati (Eastasouth Institute, 2023)
Early childhood education (PAUD) is an educational unit intended for the development of early childhood children. In the implementation of PAUD there are many problems, one of which is a lack of funding, resulting in minimal facilities available at the PAUD. Therefore, the government provides Operational Assistance (BOP) to the education units concerned. community service at the Tangerang city education office.The results of this research show that the existence of BOP is very effective and beneficial for the Early Childhood Education (PAUD) unit. This has been proven to improve the quality of education and develop previously available facilities.